Modeling and regulation of water exchange between the oxbow lake and the middle Yangtze River - Xiaoguang Liu; Shiming Yao; Zhongwu Jin; Bing Ding; Lican Ge; Shuo Guan; Weijie Wang (Ecological Informatics, 2025)
Oxbow lakes in the middle Yangtze River are critical habitats for protected species such as the Yangtze finless porpoise and play a vital role in biodiversity conservation. The impacts of the Three Gorges Dam (TGD) on hydrological processes and water exchange dynamics between these lakes and the Yangtze River were analyzed. Since the TGD began operation in 2003, significant changes in water level fluctuations and their rates of change have reshaped water exchange intensity and ecological balance in the oxbow lakes. A statistical model characterized the probability density distribution of daily water-level change rates, identifying distinct operation-dependent shifts, with the most dynamic changes near the 30 m threshold. An empirical threshold regression model incorporating the Langmuir adsorption formula effectively described the nonlinear relationships among water level, water-level change rate, and water exchange flow, providing a reliable predictive tool. Seasonal and interannual variations in water exchange intensity were quantified across three critical intervals: flood preparation (Interval I), peak fish migration (Interval II), and post-flood recession (Interval III). Findings revealed reduced water exchange during Interval II negatively impacted small fish populations, challenging species such as the Yangtze finless porpoise. Increased water exchange during Interval III improved water quality by reducing nutrient concentrations and enhancing dissolved oxygen levels. Regulation strategies using an exponential function demonstrated the potential to optimize water exchange intensity by controlling water level variation rates. The proposed ecological hydrological regulation framework offers a scientific basis for improving water exchange during key biological periods, ensuring habitat quality and supporting biodiversity. These findings highlight the critical role of hydrological regulation in maintaining the ecological health and functions of oxbow lakes.